PREDICTING SUBSEQUENT DISABILITY AMONG VULNERABLE PRIMARY CARE PATIENTS USING MOBILITY AND COGNITIVE SCREENING. (11th November 2018) - Bean, J; Jacob, M; Leritz, E; Ward, R; Leveille, S
Abstract: We aimed to examine the risk for disability as per Late Life Function and Disability Instrument (LLFDI) scores over 2 years among older adults based on mobility limitation and cognitive impairment status at baseline. Participants were classified according to gait speed (SLOW, if less than 0.8 m/s) and Mild Cognitive Impairment (MCI, based on neurocognitive test scores) into MCI-SLOW-, MCI-SLOW+, MCI+SLOW-, MCI+SLOW+ categories. Risk estimates were derived from generalized linear mixed models adjusting for socio-demographics, BMI, pain, physical activity, depression, and multimorbidity. MCISLOW profiles were differentially associated with lower limb function and participation in life roles over 2 years of follow up. When compared to MCI-SLOW-, MCI+SLOW+ participants (6.54 lower basic function and 9.79 lower advanced function) and MCI-SLOW+ (4.16, 8.65 lower) had significantly greater decline; MCI+SLOW- participants were not significantly different. However, MCI+ participants shows significant worsening of frequency of participation compared to MCI- participants irrespective of gait speed. Combined screening of mobility and cognition may provide a better assessment of disability risk and thereby better informing a plan for preventative rehabilitative care.